2017
DOI: 10.19080/ctoij.2017.03.555625
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Heel of Cancer

Abstract: Immunotherapy is the most promising trend in cancer treatments. Checkpoint inhibitors block the blocking molecules, enabling T-cells to target the cancer. MDSC-targeted immunotherapy is a new type of immunotherapy that depletes the blocking cells, enabling NK and T-cells to target the cancer. MDSC accumulates in tumor places and suppresses both adaptive and innate immunity. An oncofetal protein -AFPR -was found on host MDSC as well as on majority of cancer cells. This receptor can internalize its ligand: anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Targeting MDSCs is a new approach to immunotherapy that can eliminate immune tolerance molecules, activate NK cells, activate T cells and engage the immune system in recognizing and destroying cancer cells through a positive response ( Makkouk and Weiner, 2015 ; Pak, 2017 ). Many lines of evidence have indicated that AFP inhibits the immune response in patients with cancers ( Um et al, 2004 ; Meng et al, 2016 ; Suryatenggara et al, 2017 ; Wang and Wang, 2018 ; Zheng et al, 2020 ).…”
Section: Application Of Aif To Enhance Immunotherapy Of Cancermentioning
confidence: 99%
“…Targeting MDSCs is a new approach to immunotherapy that can eliminate immune tolerance molecules, activate NK cells, activate T cells and engage the immune system in recognizing and destroying cancer cells through a positive response ( Makkouk and Weiner, 2015 ; Pak, 2017 ). Many lines of evidence have indicated that AFP inhibits the immune response in patients with cancers ( Um et al, 2004 ; Meng et al, 2016 ; Suryatenggara et al, 2017 ; Wang and Wang, 2018 ; Zheng et al, 2020 ).…”
Section: Application Of Aif To Enhance Immunotherapy Of Cancermentioning
confidence: 99%
“…Accumulation of MDSC and AFP (native or cancer cells-origin) in cancer cells microenvironment makes immune system tolerable to cancer. That is why MDSC is a perfect target for immunotherapy [19,20] and AFP-AFPR delivery system utilization by cancer cells is its "Achilles heel" [21]. MDSC depletion breaks immune tolerance to cancer and became a new generation of immunotherapy that unleashes combined T-cells and NK attack to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the innate and adaptive immunity to destroy cancer cells and metastases [7]. This ‘Achilles-heel’ of cancer [8] was discovered and used by Govallo who achieved a 77.1% 5-year survival rate, and a 65.4% 10-year, or more, survival rate in 35 terminal patients after vaccination with the placental proteins [9], the majority of which comprised oncofetal AFP and AFPR.…”
mentioning
confidence: 99%